Sobrepeso y obesidad como factores de riesgo de diabetes mellitus tipo 2 en adultos del barrio La Quebrada, Cumbaratza - Velásquez Baho, Silvia Yulissa (2023)
Diabetes mellitus and obesity constitute a serious health problem in the 21st century, due to its excessive global growth, which makes it necessary to use tools to detect the population at risk. The objectives of the research included the classification of the adult population of La Quebrada neighborhood according to their body mass index (BMI), considering the variables age and gender. In addition, we sought to evaluate the risk of developing diabetes by applying the FINDRISK test and measuring fasting capillary blood glucose, in order to establish the correlation between type 2 diabetes mellitus and obesity. This study followed a quantitative and correlational approach, using a prospective cross-sectional field design, with a sample of 241 adults. The sample was selected through simple probabilistic sampling, after obtaining informed consent from the participants. The results revealed a high prevalence of overweight and obesity, with rates of 31.53% and 32.80% respectively in women, and 37.34% and 18.27% in young adults. Furthermore, it was observed that 50.62% of adults had a very low to low risk of developing type 2 diabetes mellitus, while 49.38% showed a moderate risk. Regarding capillary blood glucose levels, 79.93% of the participants had normal values, while 24.06% showed altered values. In conclusion, this study demonstrates a high prevalence of overweight and obesity in the population investigated, where 4 out of every 100 people can develop diabetes in the next decade according to the FINDRISK test and; 5 out of every 100 people annually according to blood glucose values. Establishing statistical significance between the test, blood glucose and BMI, which suggests the importance of addressing these risk factors comprehensively in public health strategies.